Konstruksi Media Terhadap Berita Kasus Penistaan Agama Oleh Basuki Tjahaja Purnama (Ahok): Analisis Framing Pada Surat Kabar Kompas dan Republik - Silvina Mayasari (Jurnal Komunikasi, 2017)
Religion is an important object of the news that has high political social effects, it is not independent ofthe position and the level of understanding of religion common to the community. This favorable position to encourage the mass media to consistently allocate space for preaching religious issues. The theory used is the theory of social construction of Peter L. Berger and Thomas Luckman which became known as the "social construction of mass media". The method used is the analysis of framing by Gamson and Mondigliani. This study analyzes the construction of the news media on Action 4 November 2016 and 2 December 2016 Case of Alleged Defamation of Religion by Basuki Purnama Thahaja in two (2) national newspapers, namely Kompas and Republika. Kompas on the issue of category 'Protest Demanding Law Enforcement Against Ahok or SARA?' Is not explicitly mention whether the action is legal prosecution or action SARA. Republika category of issues 'Protest Demanding Law Enforcement Against Ahok or SARA?' Mentions explicitly that this action is the action prosecution of Ahok not the action of SARA. On the issue of category 'Government Guard Protest' both Kompas and Republika expressly stated that the government oversee this action well. On the issue of category 'Effect of Protest Against the Indonesian Economy' Kompas only expressed his hope that the peaceful action will run conducive so that does not affect the business world. While Republika clearly states that non-violence would not affect the financial markets as has been predicted to run smoothly. Keywords: Construction Media, Framing, News